Comparison of thoracoscopy-guided thoracic paravertebral block and patient-controlled intravenous analgesia for postoperative analgesia after uniportal thoracoscopic pulmonary wedge resection: a prospective randomized controlled trial - Jianhui Du; Luyao Wei; Jinxian He; Xia Xu; Lihong Hu (Frontiers in Medicine)
IntroductionPatients often experience persistent, intense pain following uniportal thoracoscopic pulmonary wedge resection (UTPWR). This pain is usually intervened with patient-controlled intravenous analgesia (PCIA) or thoracoscopic-guided thoracic paravertebral block (TG-TPB), a novel peripheral nerve block technique. Herein, we compared the analgesic effects of TG-TPB and PCIA post-UTPWR.MethodsSixty patients allocated into two groups: T and P. Group T patients were administered TG-TPB with 20 mL 0.375% ropivacaine at the fourth intercostal plane before sealing the chest, and connected to a PCIA pump containing 0.9% sodium chloride (NaCl). Group P patients received TG-TPB with 20 mL 0.9% NaCl and were connected to a PCIA pump containing sufentanil. The Visual Analogue Scale (VAS) scores were recorded at 2, 6, 12, 24, 36, and 48 h postoperatively. Data on sufentanil consumption, number of PCIA presses, number of rescue analgesia interventions, adverse reactions (ARs), and the 15-item Quality of Recovery Scale (QoR-15) scores were also recorded within 24 h postoperatively.ResultsCompared to the P group, the T group showed lower VAS scores at 2, 6, 12, and 24 h postoperatively, as well as lower sufentanil consumption levels, number of PCIA presses, number of rescue analgesia interventions, and ARs incidences within 24 h postoperatively (all p < 0.05). Furthermore, the T group showed higher QoR-15 scores within 24 h postoperatively than the P group (90.5 ± 7.3 vs. 76.6 ± 6.2; p < 0.001).ConclusionCompared to PCIA, TG-TPB exerted a better analgesic effect post-UTPWR, with less opioid drug use, fewer ARs, and a significantly better recovery quality within 24 h postoperatively.Clinical trial registrationhttps://www.chictr.org.cn/, ChiCTR2000034726.